Shifts in Cutaneous Melanocytic Tumor Diagnostic Terminology: Melanocytoma, MPATH ‐Dx V2.0 and the WHO Skin5 - Duncan, Lyn M.; Elder, David E.; Piepkorn, Michael W.; Knezevich, Stevan R.; Blokx, Willeke A. M.; Bosenberg, Marcus; Busam, Klaus J.; Carr, Richard; Cook, Martin G.; Gerami, Pedram; Ko, Jennifer; Landman, Gilles; et al. (Journal of cutaneous pathology, 2025)
In this Special Issue of the Journal of Cutaneous Pathology in memory of Dr. Martin C. Mihm, Jr, we highlight his many contributions over more than 50 years to the catalog of specific melanocytic tumor terminology. Dr. Mihm was an active participant in the International Melanoma Pathology Study Group (IMPSG). Discussions led to proposed recommendations for changes in the terminology of melanocytic tumors and their standardized diagnostic reporting. Histopathological reports of melanocytic tumors provide critical information that guides patient counseling and therapy. Importantly the pathology report must relay whether the melanocytic tumor is benign, intermediate, or malignant, and when appropriate, indicate diagnostic and/or prognostic uncertainty. Recent shifts in diagnostic terminology include the recommended use of the term “melanocytoma” to describe a morphologically and genetically defined subset of intermediate risk melanocytic tumors with higher (although still very low) risk of progression compared with benign nevi. Melanocytomas are distinguished from melanocytic tumors of uncertain malignant potential (MELTUMP) which are histopathologically indeterminate or uncertain tumors. In the setting of a broad lexicon for the reporting of melanocytic tumors, an assessment tool has been developed to map existing diverse terminologies into distinct hierarchical classes. The Melanocytic Pathology Assessment Tool and Hierarchy for Diagnosis (MPATH‐Dx) V2.0 provides a four‐tiered classification scheme that is tiered by risk of tumor progression and recommended treatment. The purpose of this review is to report these shifts in diagnostic terminology, discussed and reviewed at the annual workshop of the IMPSG, in Edinburg, Scotland, in November 2022. This discussion included the use of the term melanocytoma, and the use of the MPATH‐Dx V2.0 classification and terminology for melanocytic tumors. Dr. Mihm was diligent in his attention to specific terminology, in his memory we aim to recommend terminology that improves communication in the care of those diagnosed with melanocytic tumors.